Controlled Delivery of FK506 to Improve Nerve Regeneration. (September 2016) - Labroo, Pratima; Ho, Scott; Sant, Himanshu; Shea, Jill; Gale, Bruce K.; Agarwal, Jay
Abstract : ABSTRACT: Autologous nerve grafts are the current "gold standard" for repair of large nerve gaps. However, they cause morbidity at the donor nerve site, only a limited amount of nerve can be harvested, and there is the potential for mismatches in size and fascicular patterns between the nerve stumps and the graft. Nerve conduits are a promising alternative to autografts and can act as guidance cues for the regenerating axons and allow for tension free bridging, without the need to harvest donor nerve. Separately, FK506, and FDA-approved small molecule, has been shown to enhance axon growth and peripheral nerve regeneration. This article describes the design of a novel drug delivery apparatus integrated with a poly lactic-co-glycolic acid (PLGA)-based nerve guide conduit for controlled local delivery of FK506. An FK506 dosage curve was acquired to determine the minimum in vitro concentration for optimal axonal outgrowth of dorsal root ganglion (DRG) cells, then PLGA devices were designed and tested in a diffusion chamber, and finally the bioactivity of the released media was evaluated by measuring axon growth in DRG cells exposed to the media for 72 h. The combined drug delivery nerve guide was able to release FK506 for 20 days at concentrations (1–20 ng/mL) that were shown to enhance DRG axon growth. Furthermore, the released FK506 was bioactive and able to enhance DRG axon growth. The combined drug delivery nerve guide can release FK506 for extended periods of time and enhance axon growth, and has the potential to improve nerve regeneration after a peripheral nerve injury.